Perbedaan Kadar Kolesterol Darah pada Pekerja Kantoran dan Pekerja Kasar di Desa Majasari, Bukateja, Kabupaten Purbalingga - Sandi, Christian; Saryono,; Ramawati, Dian (Jurnal Keperawatan Soedirman, 2008)
Coronary hearth disease being the major killer people in the world, that caused by cholesterol. The incidence varying between in type of occupation. This research aimed to know the difference of blood cholesterol between civil worker and labour in desa Majasari, Kecamatan Bukateja, Kabupaten Purbalingga.Analitic method with cross sectional approach used to know the difference of blood cholesterolÃ‚Â  between civil worker and labour.This research undertaken in Desa Majasari, Kecamatan Bukateja, Kabupaten Purbalingga. The population were all of civil worker and labour in Desa Majasari, that account about 105 people. Inclusion criteria were 35-60 years old, hawe being work for 10 years, male civil worker are civil servant and the labour are becak driver and Ã¢â‚¬Å“kuli panggul pasarÃ¢â‚¬Â. The exclusion criteria are diabetes melitus patient and severe infection. Sampling method used purposive sampling. The total participant was 60 people consist of 30 civil worker and 30 labour. Blood cholesterol measured by accutrend cholesterol digital (Roche TM) with mg/dl. The data collection tested with independent T-test to compare means of blood cholesterol between that groups.result.The result of this research showed that means of blood cholesterol in civil worker and labour group are 176,4 and 163,6 respectively. Independent t-test showed t = -2.511 (p=0,016), that means there is a difference of blood cholesterol between civil workerÃ‚Â  and labour group significantly.The blood cholesterol in civil worker group was higher than labour group in desa Majasari, Kecamatan Bukateja, Kabupaten Purbalingga.